Efficiency of the Controlling Application in the Corporate Management - Koval, Viktor; Kvach, Yaroslav; Makarov, Sergei (Efektywność wdrażania controllingu w zarządzaniu przedsiębiorstwem, 2010)
Controlling activity represents a difficult creative process which is based on forecasting of conditions of realization of effective administrative activity. A place, role, and process of controlling in the corporate management should be focused on the improvement of the efficiency of the management of current economic activities by application of adequate approaches and methods.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 145, s. 54-58
Keywords: efficiency; controlling application; corporate management